The Quality of goods and the rights of consumers under Malaysian law and Syariah - Amin, Naemah (2011)
The rights of consumers with regard to quality of goods or products may be regarded as the very heart of consumer protection law. It is thus well recognised under the modern statutes as well as Islamic commercial law. Consumers generally are entitled to expect that the goods supplied to them have measured up to certain standard of quality. However, in cases of product failure, the burden of proof is on a consumer to show the defective or unsatisfactory state of the good. The question then arises as to what criteria the standard of quality of goods can be assessed and determined. Can the quality be ascertained from the terms of the bargain per se? Another major issue in this regard relates to practical remedies available for consumers. Should they ask for rescission of the contract or just repair (make good of defective goods) or replacement? This paper aims to discuss consumers’ problems relating to sub-standard or low quality goods and the remedies available to them under the existing Malaysian law and Syariah. The main focus of this paper is of course the protection offers by the Malaysian Consumer Protection Act 1999 (hereinafter referred to as the CPA) and the doctrine of al-khiyar al-aib (option of defect) under Islamic law.